Effect of Silica Nanoparticles on Wormlike Micelles with Different Entanglement Degrees. Issue 3 (31st January 2019) - Zhao, Mingwei; Gao, Zhibin; Dai, Caili; Sun, Xin; Zhang, Yue; Yang, Xiujie; Wu, Yining
Abstract: Enhancing the viscoelastic properties of wormlike micelles by adding nanoparticles has been widely reported. Various mechanisms have been proposed to explain how nanoparticles strengthen the network formed by wormlike micelles. It remains unclear whether nanoparticles produce the same effect on systems with different entanglement degrees. To clarify this issue, the concentration of potassium chloride was used to control the entanglement degree of wormlike micelles. The rheological behavior of different nanoparticle‐enhanced wormlike micellar systems (NEWMS) was investigated using rheology. Three critical parameters including zero‐shear viscosity ( η 0 ), relaxation time ( τ R ), and contour length ( L ) were calculated to analyze the effect of nanoparticles on the different wormlike micellar systems. An appropriate mechanism describing the interaction between nanoparticles and wormlike micelles with different structures was proposed.